Características de carcaça de caprinos canindé submetidos à restrição alimentar - Bezerra, Andreia Batista; Neto, Severino Gonzaga; de Medeiros, Ariosvaldo Nunes; de Carvalho, Francisco Fernando Ramos; Bispo, Safira Valença; Souza, Anaiane Pereira [UNESP]; Neto, José Maurício dos Santos; Ribeiro, Luana Paula dos Santos (FapUNIFESP (SciELO), 2017)
This study aimed to evaluate the effects of feed restriction on the carcass characteristics of castrated Canindé goat kids. A randomized block design was used, in which 21 goat kids with a body weight (BW) of 15.9±1.0kg were allocated to three levels of feed restriction: ad libitum, 20% and 40% restriction related to the ad libitum intake. The diet consisted of 55% forage (Tifton) and 45% concentrate. All animals were slaughtered when the kids fed ad libitum reached a BW of 25kg. After slaughter, the carcasses were chilled for 24 hours and subsequently measured. Kids fed ad libitum and subjected to 20% feed restriction showed similar morphometric carcass measurements, except for the chest circumference. Goat kids fed ad libitum exhibited greater values for warm and cold carcass yields compared with those subjected to 40% feed restriction and did not differ from the kids under 20% feed restriction. Weights of the commercial cuts showed decreasing mean values according to the intensity of feed restriction. Castrated Canindé goat kids subjected to 20% feed restriction presented similar carcass yields and proportion of commercial cuts to those fed ad libitum.
Carcass characteristics of canindé goats subjected to feed restriction
Keywords: Carcass yield; Commercial cuts; Native breed